Cultivation of Entamoeba histolytica in vitro and diagnose the bacterial growths in culture media (Baghdad Science Journal, 2009)
The parasite was isolated from a stool sample, cultivated and maintained in vitro using Locke-egg medium (LEM) and Liver infusion agar medium (LIAM) . The culture was maintained for up to 21 months, and the best time to maintain the parasite was every 48 hours, although the growth in the culture media continued for 13 days without a maintenance. Additionally, no cyst formation was observed during cultivation of parasite in the two culture media. Although, was observe young cyst formed in LEM media were deletion of maintained. The diagnosis of bacteria growth in the culture media, bacterial content (Escherichia coli) was an dominance and essential requirement for a successful cultivation of Entamoeba histolytica in the two culture media.